Strategi Pengembangan Mutu Sumberdaya Guru MISS Putri Sukorejo - Abdullah, Abdullah (Program Pascasarjana Universitas Ibrahimy, 2017)
The success in the development of national education sector needs to be supported by the various components and elements that exist in the education system. One of the most important elements in the education system is the availability of qualified human resources. Organizationally, the factor of human resources has a strategically important position in addition to other educational factors. This study, focused on the development strategy of the quality of teacher resources, using a qualitative approach. This study, focused on the development strategy of the quality of teacher resources, using a qualitative approach. The efforts and strategic steps MISS Putri Sukorejo in the development of quality resource teachers are as follows: a) Making the Vision, Mission and Objectives MISS Putri Sukorejo as target quality development resource teacher, b) Build teacher commitment, c) Building a Discipline, d) Meet the Teachers' Welfare, e) Changing Mindsets teacher / positive Character Building. Based on some analysis that we can know that the shape and development of quality resource strategy techniques MISS Putri Sukorejo teacher may be classified typology academy is a strategy used by attempting to develop